Adsorption and Desorption Characteristics of Cd2+ and Pb2+ by Micro and Nano-sized Biogenic CaCO3 - Liu, Renlu; Guan, Yong; Chen, Liang; Lian, Bin (Frontiers in Microbiology, 2018)
The purpose of this study was to elucidate the characteristics and mechanisms of adsorption and desorption for heavy metals by micro and nano-sized biogenic CaCO3 induced by Bacillus subtilis, and the pH effect on adsorption was investigated. The results showed that the adsorption characteristics of Cd2+ and Pb2+ are well described by the Langmuir adsorption isothermal equation, and the maximum adsorption amounts for Cd2+ and Pb2+ were 94.340 and 416.667 mg/g, respectively. The maximum removal efficiencies were 97% for Cd2+, 100% for Pb2+, and the desorption rate was less than 3%. Further experiments indicated that the biogenic CaCO3 could maintain its high adsorption capability for heavy metals within wide pH ranges (3–8). The FTIR and XRD results showed that, after the biogenic CaCO3 adsorbed Cd2+ or Pb2+, it did not produce a new phase, which indicated that biogenic CaCO3 and heavy metal ions are governed by a physical adsorption process, and the high adsorptive capacity of biogenic CaCO3 for Cd2+ and Pb2+ were mainly attributed to its large total specific surface area. The findings could improve the state of knowledge about biogenic CaCO3 formation in the environment and its potential roles in the biogeochemical cycles of heavy metals.